2013
DOI: 10.4028/www.scientific.net/amm.361-363.1875
|View full text |Cite
|
Sign up to set email alerts
|

Lane Change Decision Analysis Based on Drivers' Perception-Judgment and Game Theory

Abstract: To clearly understand the mechanism of drivers lane-changing decision, based on drivers perception of external information, integrated cognitive judgment and game theory, the decision-making model was established, then the structure and operating mechanism of the model were detailedly analyzed. By introducing game theory-related knowledge, the non-cooperative mixed strategy game between the object vehicle and the following vehicle in the target lane was further discussed. Then, the benefits and Nash equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In addition, factors such as continuous driving time, age, and driving seniority can affect the driver's speed and distance perception [22]. The researchers also suggested that even veteran drivers tend to underestimate their driving speed while commuting [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, factors such as continuous driving time, age, and driving seniority can affect the driver's speed and distance perception [22]. The researchers also suggested that even veteran drivers tend to underestimate their driving speed while commuting [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For humandriven vehicles, Kita first built a mixed strategy game model for vehicles on the highway according to the time to collision [3]. On this basis, the risk conflicts [4], safety and efficiency of lane changing [5][6][7], driving space [8], and lane-changing requirements [9] were considered in the mixed strategy lanechanging game models on the highway or urban streets. Kang and Rakha [10] proposed a repeated game model by calculating the accumulated payoffs for the players so as to explore the impacts of the history of the players' decisionmaking on the choice of strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Lane change warning systems (LCW) are gradually being developed and popularized in vehicle active safety systems [11,12]. By monitoring the surrounding vehicles and issuing collision warnings to the driver in advance, the system reduces the risk of potential conflict, improves land change safety, and reduces the driver's operating load [13][14][15]. According to the collected road and traffic information, current LCWs generally utilize the safety lane change evaluation algorithm to determine whether the driver will encounter danger during the lane change process.…”
Section: Introductionmentioning
confidence: 99%